The Influence of Leadership and Work Culture on Employee Loyalty at Wedding Organizer XYZ in Sleman Regency - Nur Aeinun Nisya (Indonesian Journal Publisher, 2024)
This study aims to find out: (1) the influence of leadership on employee loyalty at Wedding Organizer XYZ in Sleman; (2) the influence of work culture on employee loyalty at Wedding Organiser XYZ in Sleman; (3) the simultaneous influence of leadership variables and work culture on employee loyalty at Wedding Organiser XYZ in Sleman. This research is a survey research. The sampling technique in this study is a saturated sample technique, the sample in this study is all employees of wedding organizer XYZ in Sleman which totals 38 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression analysis. The results of the study showed that (1) leadership had a partially significant positive effect on the loyalty of Wedding Organizer XYZ employees in Sleman district (t count = 2.551; significance 0.015 < 0.05 and β = 0.429); (2) work culture has a partially significant positive effect on the loyalty of Wedding Organizer XYZ employees in Sleman district (t count = 3.574; significance 0.001 < 0.05 and β = 0.559); (3) there was a simultaneous influence between leadership and work culture on the loyalty of Wedding Organizer XYZ employees in Sleman Regency (F count = 21.932 and significance 0.000 < 0.05).